Ask questions and get helpful answers.

Find the second, fourth, and eleventh terms of sequence described by the rule.

A(n) = 3 + (n - 1)(5)
--------------------------------
A(n) = 3+ (n-1)5
A(2) = 3 + (2 - 1) × 5
A(2) = 3 + 1 × 5
A(2) = 3 + 5
A(2) = 8

Next, I had to find A(4)= ?
So what, I did was:

A(n) = 3 + (n - 1)5
From A (4), n = 4
A(4) = 3 + (4 - 1) × 5
A(4) = 3 + 15
A(4) = 18

However now, I need to find A(11) = ?
Please help me find A(11) = ?

  1. 👍
  2. 👎
  3. 👁
  4. ℹ️
  5. 🚩

1 answer

  1. once is enough, please
    Repeated postings will not get faster or better responses.

    1. 👍
    2. 👎
    3. ℹ️
    4. 🚩

Answer this Question

Related Questions

Still need help?

You can ask a new question or browse existing questions.